Pesticide Options for Important Insect, Mite, and Mollusk Pests of Commercial Flowers in Florida - James F. Price; Curtis Nagle (EDIS, 2012)
Effective arthropod pest management in commercial floral crops requires that pests be detected in a timely manner through systematic scouting and that appropriate control measures be applied as conditions warrant. Control measures may include economical combinations of cultural controls, physical controls, biological controls, and chemical controls. This revised 9-page guide is a summary of chemical control measures that are presently available to commercial flower producers in Florida and includes beneficial nematode and microbial insecticides that also are components of biological control. Written by James F. Price and Curtis Nagle, and published by the UF Department of Entomology and Nematology, November 2012.